Crystal structures and enhancement of photoluminescence intensities by effective doping for lithium tantalate phosphors. Issue 4 (2nd September 2015) - Ichioka, Hiroaki; Furuya, Shohei; Asaka, Toru; Nakano, Hiromi; Fukuda, Koichiro
Abstract : Crystal structures of (Li0.925 Eu 3+ 0.025 )TaO3, (Li0.968 Eu 3+ 0.032 )(Ta0.81 Ti0.19 )O2.937, (Li0.967 Sm 3+ 0.033 )(Ta0.89 Ti0.11 )O2.978, and (Li0.950 Sm 3+ 0.033 Mg0.017 )(Ta0.89 Ti0.11 )O2.987 were investigated by X-ray powder diffraction. The initial structural parameters, taken from those of the isomorphous compound (Li0.977 Eu 3+ 0.023 )(Ta0.89 Ti0.11 )O2.968 (space group R 3 c and Z = 6), were refined by the Rietveld method. A pattern-fitting method based on the maximum-entropy method was subsequently used to determine the three-dimensional electron-density distributions (EDDs) that are free from the structural bias. We confirmed that the EDDs are in accord with the resulting structural models, each of which was composed of the [(Ta, Ti)O6 ] octahedron and [(Li, Eu, Sm, Mg)O12 ] polyhedron. We compared these polyhedra and found that the prominent difference among these compounds was the centroid-to-(Li, Eu, Sm, Mg) distance (eccentricity) of [(Li, Eu, Sm, Mg)O12 ]. The high correlation was demonstrated between the magnitude of eccentricity and photoluminescence intensity under near ultraviolet excitation.